Adobe After Effects CC : 2014 release - Faulkner, Andrew; Gyncild, Brie (Classroom in a book., 2015)
Contains 14 lessons that cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you.